The For-Profit Motive - Bernasconi, Andres (International Higher Education, 2013)
For-profit higher education is controversial. The legitimacy of the profit motive in education is called into question by those who believe that a trust-based relationship cannot be mediated by economic gain. Proponents of education as a legitimate business, for their part, argue that competition and market discipline are at once good for business and for quality education. They also maintain that in the absence of profit-seeking entrepreneurship we would not be seeing the enormous expansion of enrollments characteristic of higher education in the developing world. At any rate, if the nature of the institution is to be a choice for students, they need to be properly informed about whether the institution of their choice is for-profit.